(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2026)
The current study attempts to design for the development of Samarra’s Old District. It is a mirror that reflects the effects of this civilization and the expression of the city’s symbols through the integrated development of the examined region and its significance. Which will become a tourist attraction due to its cultural significance. It is also economically significant because it helps to the city’s economic development and provides job possibilities for the unemployed. Which instills in the visitor a new perception of Samarra and, at the same time, instills pride in the city’s youth when the heritage of their city is revealed to them. The archaeological significance of the project is one of the grounds for its selection. The reasons for choosing the project 1-The archaeological significance of the ancient district, which is a strong point for attracting tourists to the city and aids in the identification of the city’s legacy. 2-To attract tourists, the city requires a space and an entertainment facility that welcome their activities and fits their needs. Project goals and objectives 1. Create communities near the Grand Mosque and give them their unique identity through a panorama that recounts the city’s past to visitors and residents, as well as allowing them to see the heritage and glory of their forefathers. 2. Hold creative performances to communicate with other people’s civilizations and cultures, as well as global scientific and technological growth. Visitors’ definitions of Samarra’s extended heritage, as well as the city’s residents’ definitions of what exists overseas and how it reflects current cultural development. Provide trade centers for various types of heritage goods, which is a lovely souvenir that visitors can preserve, and there can be. The research made a Sustainable development plan for the studied area and recommended some proposals for completion of the project.